2015
DOI: 10.1097/aog.0000000000000801
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supervised Prenatal Exercise on Fetal Growth

Abstract: These data demonstrate that structured prenatal exercise reduces the risk of having a large newborn without a change in the risk of having a small newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
117
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 50 publications
9
117
0
4
Order By: Relevance
“…4,6,25 Our results suggest that pregnant women who exercise at high levels, have increased odds of having a placenta among the 5% smallest. Thus, our findings suggest that high exercise frequency may lead to a shift in the placental weight distribution towards smaller placentas.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…4,6,25 Our results suggest that pregnant women who exercise at high levels, have increased odds of having a placenta among the 5% smallest. Thus, our findings suggest that high exercise frequency may lead to a shift in the placental weight distribution towards smaller placentas.…”
Section: Discussionmentioning
confidence: 53%
“…High frequency of exercise in pregnancy has been associated with a slightly lower mean birthweight [3][4][5][6] and with reduced risk of having a newborn with high birthweight. 4,6,25 Our results suggest that pregnant women who exercise at high levels, have increased odds of having a placenta among the 5% smallest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent large-scale meta-analysis on the impact of chronic exercise on fetal growth (28 randomized controlled trials/5322 infants) demonstrate no increased risk of small infants, and in fact showed that maternal exercise resulted in a 31% reduction in the risk of large babies. 21 These findings suggest that maternal adaptations exist to maintain adequate glucose delivery to the fetus during exercise.…”
Section: Hormone and Substrate Adaptations To Prenatal Exercisementioning
confidence: 96%
“…2 These benefits include improved fitness, 3 prevention of excessive gestational weight gain, 4 obesity/weight retention, 5 gestational diabetes, 6 hypertension, 4 maternal depression, 7 and reduction in cesarean section rates. 4 Furthermore, maternal exercise has been linked to appropriate fetal weight gain 8 and prevention of chronic disease development in the offspring. 9 In contrast, physical inactivity and sedentary behavior have been associated with obesity and its comorbidities, diabetes, hypertension, 4 cardiovascular disease, metabolic syndrome, and depression.…”
Section: Introductionmentioning
confidence: 99%